Design and Development of Ocean Monitoring System Based on Global Positioning System - Mohd Salleh, Anuar (International Journal of Integrated Engineering, 2019)
Coastal zone of Malaysia has a vital role in socio-economic and environmental in pursuing the country development. However, it constantly faces a threat from coastal erosion. Hence, this study focused on developing the ocean monitoring system consists of a buoy with Global Positioning System (GPS) technology, reference station and data analysis techniques. Based on the verification with slider machine, this system has been able to provide high accuracy result less than 0.5 cm compared to the standard value of slider machine. This study presents the capabilities of GPS buoy to observe wave data at Strait of Malacca by using high precision kinematic positioning approach. The GPS buoy data obtained from this observation were processed through a precise, medium-range differential kinematic technique. The RMS error from data analysis technique is less than 0.0016 m. Validation with Department of Survey and Mapping Malaysia (JUPEM) automatic tide gauges have found both methods agreed on tidal pattern with small discrepancy of less than 10 cm. Encouraging results were also obtained when the tidal observations off coast Senggarang was done. The tidal pattern for each observation has successfully recorded with acceptable accuracy when compared with manual observation. The kinematic coordinates further used to calculate the magnitude of the Power Spectral Density (PSD). PSD analysis function able to shows the strength of the variations (energy) as a function of frequency. The tidal changes and monsoon wind have been found to greatly influence the wave energy as shown in the PSD analysis. From the test result, GPS buoy and data processing technique promises a total solution as a complete ocean wave monitoring solution.